Investigating the influence of 'losses disguised as wins' on decision making and motivation in rats. Issue 8 (December 2018) - Ferland, Jacqueline-Marie N.; Adams, Wendy K.; Murch, Spencer; Wei, Linda; Clark, Luke; Winstanley, Catharine A.
Abstract : Multiline slot machines encourage continued play through 'losses disguised as wins' (LDWs), outcomes in which the money returned is less than that wagered. Individuals with gambling problems may be susceptible to this game feature. The cognitive and neurobiological mechanisms through which LDWs act are unknown. In a novel rat operant task, animals chose between a 'certain' lever, which always delivered two sugar pellets, or an 'uncertain' lever, resulting in four sugar pellets on 50% of trials. LDWs were then introduced as a return of three sugar pellets on 30–40% of uncertain rewarded trials. For half the rats, winning outcomes were paired with audiovisual feedback (cues). In a second study, the basolateral amygdala (BLA) was inactivated during initial presentation of LDWs. While LDWs shifted most rats' choice toward the certain lever, a subgroup of LDW vulnerable rats continued to choose the uncertain option, when the reward rate diminished. This profile of LDW vulnerability was reproduced after inactivating the BLA. Persistent choice of uncertain outcomes despite lower reward rates may reflect impaired functioning within the BLA. Future work using this model may provide insight into the neurobiological mechanisms contributing to the motivational properties of LDWs and their contribution to problematic gambling.